Digital Assistants: AI to Reduce Teachers' Expectations of Reality Shock - Karabatak, Songul; Alanoglu, Muslim; Kuloglu, Aysenur; Bozkurt, Ezgi (Institute of Electrical and Electronics Engineers Inc., 2025)
This research emphasizes the importance of integrating AI technologies into teacher training programs, highlighting the potential solutions these tools provide for common issues faced during teachers' early professional years. Through qualitative analysis of semi-structured interviews with computer science teachers, this study identifies teachers' purposes for using AI tools, essential features digital mentoring assistants should possess, and how these systems could support professional development. Findings indicate teachers primarily use digital assistants for academic tasks, general research, educational practices, and student support. Key recommendations for AI mentoring assistants include cultural adaptability, realistic simulations, emotional and psychological support, easy accessibility, and facilitating interaction with experienced mentors. Overall, the research underscores AI's promising role in teacher education, calling for well-structured, accessible AI mentoring systems to effectively support teachers' adaptation processes. © 2025 IEEE.
13th International Symposium on Digital Forensics and Security, ISDFS 2025 -- 24 April 2025 through 25 April 2025 -- Boston -- 209331
Keywords: artificial intelligence; digital assistant; Reality shock; teacher